2022
DOI: 10.1093/jas/skac355
|View full text |Cite
|
Sign up to set email alerts
|

Guanidinoacetic acid supplementation improves intestinal morphology, mucosal barrier function of broilers subjected to chronic heat stress

Abstract: The current study is designed to investigate dietary guanidinoacetic acid (GAA) supplementation on the growth performance, intestinal histomorphology, and jejunum mucosal barrier function of broilers that subjected to chronic heat stress (HS). A total of 192 male broilers (28-d-old) were randomly allocated to four groups. A chronic HS model (at a temperature of 32 °C and 50 to 60% relative humidity for 24 h daily) was applied in the experiment. Normal control (NC, ad libitum feeding, 22°C), heat stress group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…This was consistent with the finding that AGAT can be feedback-inhibited by GAA [ 37 ]. Most metabolic studies on GAA have focused on the liver, blood, urea, and small intestinal segment mucosa [ 8 , 36 , 38 ]. The addition of GAA increased the rumen GAA content at both stages 1 and 2, confirming that GAA was degraded in the rumen and significantly correlated with the degradation rate (UGAA, 50.9%; CGAA, 15.8%).…”
Section: Discussionmentioning
confidence: 99%
“…This was consistent with the finding that AGAT can be feedback-inhibited by GAA [ 37 ]. Most metabolic studies on GAA have focused on the liver, blood, urea, and small intestinal segment mucosa [ 8 , 36 , 38 ]. The addition of GAA increased the rumen GAA content at both stages 1 and 2, confirming that GAA was degraded in the rumen and significantly correlated with the degradation rate (UGAA, 50.9%; CGAA, 15.8%).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the ME level did not modify the morphological characteristics of the duodenum. However, GAA supplementation increased the width of the villi and the depth of the crypts and decreased the height of the villi, which is contrary to what was reported by Peng et al in 2003, in which an improvement in intestinal morphology was observed in broilers subjected to heat stress supplemented with 0.6 g/kg of GAA [ 36 ]. It has been shown that the length of the villi improves the absorption capacity of nutrients in the intestine and that deep crypts indicate high metabolic activity in the tissue, so modifications in these characteristics may indicate a reduction in the absorption of nutrients [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 61%
“…Growth performance is an important indicator for evaluating whether the production efficiency of poultry meets people’s expectations. The decrease in growth performance caused by heat stress is related to decreased food intake ( Peng et al, 2023 ). The result of this study indicated that heat stress reduced the weight and ADG of broilers but had no effect on ADFI and FCR.…”
Section: Discussionmentioning
confidence: 99%